Basic psychic personality structure as a precondition for reaching endurance performance limits using triathlon as an example - Kovárová, L.; Nováková, K.; Kovár, K.; Pánek, D. (Journal of Outdoor Activities, 2013)
The aim of this paper was to explore the differences in the basic psychic personality structure between elite level and hobby triathletes. The total of 63 triathletes (44 men and 19 women) participated in the research. We used the SPARO personality questionnaire from the Diaros psychodiagnostic testing battery. The unpaired t - test was used for data analysis in SPSS. The results of this study confirmed some differences in the basic psychic personality structure between top performance and hobby male and female triathletes. Statistically significant differences in men (p = 0,05, or p = 0,01 respectively) are mainly found in the dimension of integration, then in self-assertion (p = 0,05) and correctiveness. In women, it is the dimension of normality (p = 0,05) and also self-assertion (p = 0,1); here, however, the relationship between the surveyed groups is reverse. There is a weaker tendency towards self-assertion among top performance female triathletes.